Incentives and barriers to HIV testing among female sex workers in Ceará - Martins,Telma Alves (2018)
ABSTRACT OBJECTIVE Estimating HIV prevalence and describing the incentives and barriers for HIV testing among female sex workers. METHODS This cross-sectional study recruited 402 women aged 18 years or older, residing in Fortaleza, state of Ceará, Brazil, who reported having had sexual intercourse in exchange for money in last four months. The sample was recruited using Respondent Driven Sampling, between August and November 2010. RESULTS The 84.1% of the sample tested and the estimated prevalence of HIV infection was 3.8%. The sample was young (25 to 39 years ), single (80.0%), with one to three children (83.6%), had eight or more years of schooling (65.7%), and belonged to social classes D/E (53.1%). The majority worked in fixed locations (bars, motels, hotels, sauna - 88.9%), and prostitution was their only source of income (54.1%). About 25% of the sample did not know where to test in the public health sector and 51.8% either never tested or hadn’t tested for over a year or more. The main reported barriers to testing were the perceptions that there was no risk of becoming infected (24.1%), and, alternatively, fear of discrimination if the test was positive (20.5%). Incentives for testing were the greater availability of testing sites (57.0%) and health facilities with alternative schedules (44.2%). CONCLUSIONS Prevalence for HIV was similar to that found in other Brazilian cities in different regions of the country, although higher than the general female population. Non-traditional venues not associated with the health system and availability of testing in health units during non-commercial hours are factors that encourage testing. Not considering oneself to be at risk, fear of being discriminated against and not knowing testing locations are barriers.